PHYSICAL AND ANATOMICAL PROPERTIES OF Hevea brasiliensis CLONES - de Lima, Israel Luiz; Moreira, Izabella Vicentin; Ranzini, Maurício; Longui, Eduardo Luiz; Cambuim, José [UNESP]; de Moraes, Mario Luiz Teixeira [UNESP]; Garcia, José Nivaldo (Universidad del Bio Bio, 2023)
Our goal was to determine physical properties and anatomical features in 33-year-old Hevea brasiliensis clones. We cut wood samples from clones LCB510, RRIM600, IAN873, IAN717 and GT1 planted in Selvíria, Mato Grosso do Sul, Brazil. We used standard techniques in wood studies. We found that clones differ in basic density, volumetric shrinkage and anatomical features, with the exception of ray width. Basic density, volumetric shrinkage, fiber length, fiber wall thickness, vessel element length and vessel diameter tended to increase from pith to bark, while vessel frequency propended to decrease. We conclude that wood of the studied clones has potential for industrial use.
Keywords: Basic density; cell dimensions; radial variation rubber tree; volumetric shrinkage